KOMUNIKASI PEMBELAJARAN GURU KEPADA MURID DALAM MEWUJUDKAN SEKOLAH RESPONSIF GENDER PADA SMA NEGERI 4 KOTA PEKANBARU - Wawan Gunawan; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
SMA Negeri 4 Pekanbaru has made gender responsive schools one of the school's flagship programs shown through the vision and mission of SMA Negeri 4 Pekanbaru. Creating a gender responsive school environment is not an easy thing, teachers must implement gender responsiveness in learning activities so that the growth of character between students to respect gender differences. The purpose of this study was to determine the learning methods used, school facilities that are gender responsive and the obstacles that occur in learning communication in realizing gender responsive schools in SMA Negeri 4 Pekanbaru.This study used qualitative research methods. Determination of informants using purposive techniques. Data collection techniques consist of interviews, observation, and documentation. While the data analysis technique uses descriptive analysis according to Huberman and Miles. The data validity checking technique used in this study is the extension of participation, triangulation.The results showed that the application of gender responsiveness in learning communication was seen in 5 methods namely lecture method, question and answer method, practice or demonstration method, discussion and presentation method, and assignment method. Meanwhile school facilities that are gender responsive are learning communication media consisting of audio media, visual media and audiovisual media. Other gender-responsive school facilities, namely, the arrangement of classrooms that pay attention to the special needs of male and female students in the classroom, school toilets that are designed to be safe to avoid breakdowns and sexual harassment in toilets, and the number of female toilets is greater than male toilets in which there are clothes hangers, trash cans and mirrors, and there are special spaces that are separated in order to create comfort in the school environment such as counseling booths, UKS rooms, parking lots, worship spaces and places of ablution. During running this program there are several obstacles that occur in communication of gender responsive learning. These are the obstacles of lack of community participation, psychological barriers and barriers to communicators. Keyword: Learning Communication, Gender Responsive, Critical Pedagogy.